High-efficiency degradation low-density magnesium-based alloy as well as preparation method and application thereof

By using a low-density magnesium-based alloy with Li: 5.7-10.3%, Gd: 2-6%, Ni: 0.5-1.5%, and a balance of Mg, a highly efficient degradable fracturing ball was prepared by vacuum induction smelting and casting, and the solution was solved. The fracturing ball degradation speed and density problems in the prior art have been made, and more efficient oil production has been achieved.

CN119287233APending Publication Date: 2025-01-10HARBIN ENG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310836927.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-10
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The existing degradable magnesium-based alloys for fracturing balls are difficult to take into account the simple process, the efficient degradation rate and the controllable degradation rate, and the density is relatively high and is not suitable for underground ball mounts, which affects oil production efficiency.

Method used

Using a low-density magnesium-based alloy with Li: 5.7-10.3%, Gd: 2-6%, Ni: 0.5-1.5%, and a balance of Mg, it is melted and cast and molded through a vacuum induction melting furnace to form a high-efficiency degradation of low-density magnesium-based alloy. Alloy, fracturing balls with compression strength of 100-150MPa are prepared, suitable for rapid downhole dissolution.

Benefits of technology

The plastic toughness, specific strength and corrosion degradation rate of fracturing balls are improved, and faster degradation speed and higher mechanical strength are achieved, which is suitable for petroleum production needs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119287233A_ABST
    Figure CN119287233A_ABST
Patent Text Reader

Abstract

The invention discloses an efficient degradation low-density magnesium-based alloy and a preparation method and application thereof. The invention belongs to the technical field of magnesium-based alloys for fracturing balls. The technical problems that an existing fracturing ball is high in density and difficult to flow back or drill and mill after being used are solved. According to the Mg-Li-based alloy provided by the invention, the proportion of Mg, Gd and Ni is reasonably regulated and controlled, so that the fracturing ball prepared from the degradable Mg-Li-based alloy has the advantages of good plasticity and toughness, high specific strength, high pressure bearing capacity and high primary corrosion degradation rate, the fracturing ball can be quickly dissolved underground after fracturing operation is completed, the efficiency of the fracturing operation is effectively improved, and the fracturing cost is reduced. Therefore, the petroleum production efficiency is greatly improved, and the petroleum production cost is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of magnesium-based alloys for fracturing balls, and in particular relates to a highly efficient degradable low-density magnesium-based alloy and a preparation method and application thereof. Background Art

[0002] Oil and gas exploration and exploitation are becoming increasingly difficult, with complex storage conditions, low permeability, and poor economic benefits. Horizontal well staged fracturing technology is an important technology to solve the problem of oil resource exploitation. Staged fracturing tools play an important role. Fracturing balls are plugging tools for horizontal wells during staged fracturing, and play a key role in improving oil and gas production efficiency. Fracturing balls usually work in a high-temperature and high-pressure environment. Due to production process limitations, fracturing balls need to have a lower density. During the fracturing process, pressure needs to be applied to the formation, so they need to withstand a pressure of about 70MPa.

[0003] Fracturing ball flowback or drilling and milling is a difficult and risky step in the oil production process, and it greatly reduces the efficiency of oil production. Therefore, the use of biodegradable materials to prepare fracturing balls allows the workpiece to dissolve quickly underground after the fracturing operation is completed, which can improve the efficiency of the fracturing operation and reduce the cost of oil production.

[0004] However, the degradable magnesium-based alloy used in fracturing balls currently has difficulty in taking into account the characteristics of simple process, efficient degradation rate and controllable degradation rate. In addition, during the production process, the fracturing ball needs to enter the ball seat with the fracturing fluid, so a material with a lower density is needed to better fit into the ball seat. The alloy used in the fracturing ball materials studied in China has a higher density, so it is particularly important to develop a material that is more suitable for fracturing balls. Summary of the invention

[0005] In order to overcome the deficiencies of the prior art, the present invention provides a highly efficient degradation of low-density magnesium-based alloy and a preparation method and application thereof.

[0006] The purpose of the present invention is to achieve the following technical solutions:

[0007] One of the purposes of the present invention is to provide a highly efficient degradable low-density magnesium-based alloy, wherein the highly efficient degradable low-density magnesium-based alloy is composed by mass fractions of: Li: 5.7-10.3%, Gd: 2-6%, Ni: 0.5-1.5%, and the balance is Mg.

[0008] It is further defined that the high-efficiency degradable low-density magnesium-based alloy is composed by mass fractions of: Li: 8%, Gd: 4%, Ni: 1.5%, and the balance is Mg.

[0009] The second object of the present invention is to provide a method for preparing a magnesium-based alloy with high efficiency and low density, wherein the method is carried out according to the following steps:

[0010] Pure Mg, pure Li, Mg-Gd alloy and Mg-Ni alloy are used as raw materials, which are melted in a vacuum induction melting furnace and then cast into shape.

[0011] It is further defined that the Mg-Gd alloy is Mg-30%Gd, and the Mg-Ni alloy is Mg-30%Ni.

[0012] It is further defined that pure Ar is used as the protective gas during the smelting process.

[0013] The smelting process is further defined as: heating from room temperature to 150-200°C and keeping warm for 5 minutes, then heating to 400-450°C and keeping warm for 5 minutes, and finally heating to 720°C and keeping warm.

[0014] The third object of the present invention is to provide an application of a highly efficient degradation low-density magnesium-based alloy in the preparation of fracturing balls.

[0015] A fourth object of the present invention is to provide a method for preparing a fracturing ball, the method comprising: machining the above-mentioned high-efficiency degradable low-density magnesium-based alloy into a fracturing ball.

[0016] A fifth object of the present invention is to provide a fracturing ball prepared according to the above preparation method, wherein the fracturing ball has a compression strength of 100-150 MPa.

[0017] It is further defined that the dissolution rate of the fracturing ball in a 3% KCl aqueous solution at 25°C is 0.155-0.36 mg / cm 2 ·min, hydrogen evolution rate is 0.16-0.37mL / cm 2 ·min.

[0018] Compared with the prior art, the present invention has the following significant effects:

[0019] The fracturing ball made of the degradable Mg-Li-based alloy prepared by the present invention has good plastic toughness, high specific strength, strong pressure bearing capacity, and high corrosion degradation rate. The specific advantages are as follows:

[0020] (1) The present invention provides a Mg-Li based alloy, wherein the lithium content of the dual-phase matrix component is selected so that a large number of phase interfaces exist between the matrix phases alfa (Mg) and Beta (Li), thereby forming a large number of micro-batteries, which greatly improve the corrosion rate of the alloy. In addition, the corrosion rate is effectively increased by adjusting the galvanic corrosion between the second phase and the magnesium-lithium alloy matrix, so that the degradation rate of the fracturing ball is greatly increased compared with conventional magnesium alloys.

[0021] (2) Ni is a typical alloying element that promotes corrosion of magnesium alloys. Adding Ni elements that promote corrosion to magnesium alloys further increases the corrosion rate of the alloy. In addition, more importantly, the present application forms a large number of long-period stacking ordered phases (LPSO) with higher potentials by reasonably regulating the ratio of Mg, Gd, and Ni. There is a large electronegativity difference between the LPSO phase and the magnesium matrix. Not only does LPSO have an interface between the phases and the matrix, but there are also a large number of interfaces between the lamellar results inside the LPSO, thus forming a large number of micro-batteries, which greatly promotes the degradation of the alloy material. At the same time, the long-period ordered stacking phase (LPSO) as the second phase in the magnesium-lithium alloy can also effectively improve the mechanical strength of the magnesium-lithium alloy. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 Optical microscopic images of fracturing balls obtained in Examples 1-3 and Comparative Example 1; wherein a-Comparative Example 1, b-Example 3, c-Example 2, d-Example 1;

[0023] Figure 2 The XRD diffraction patterns of the fracturing balls obtained in Examples 1-3 and Comparative Example 1;

[0024] Figure 3 The compressive stress-strain curves of the fracturing balls obtained in Examples 1-3 and Comparative Example 1;

[0025] Figure 4 The weight loss rate of the fracturing balls obtained in Examples 1-3 and Comparative Example 1 in a 3% KCl solution;

[0026] Figure 5 The hydrogen evolution volume and hydrogen evolution rate of the fracturing balls obtained in Examples 1-3 and Comparative Example 1 in 3% KCl solution over time; wherein a-hydrogen evolution volume, b-hydrogen evolution rate;

[0027] In the accompanying drawings, Mg-8Li-4Gd-1.5Ni represents Example 1, Mg-8Li-4Gd-1Ni represents Example 2, Mg-8Li-4Gd-0.5Ni represents Example 3, and Mg-8Li-4Gd represents a comparative example. DETAILED DESCRIPTION

[0028] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0029] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, methods and instruments used are conventional materials, reagents, methods and instruments in the art unless otherwise specified, and can be obtained through commercial channels by those skilled in the art.

[0030] The terms "comprising," "including," "having," "containing," or any other variations thereof, as used in the following examples, are intended to cover a non-exclusive inclusion. For example, a composition, step, method, article, or apparatus comprising the listed elements is not necessarily limited to only those elements, but may include other elements not expressly listed or inherent to such composition, step, method, article, or apparatus.

[0031] When equivalent, concentration or other value or parameter is represented by the range limited by range, preferred range or a series of upper preferred value and lower preferred value, this should be understood as specifically disclosing all ranges formed by any pairing of any upper range limit or preferred value and any lower range limit or preferred value, regardless of whether the scope is disclosed separately. For example, when disclosing range "1 to 5", described range should be interpreted as including range "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5" etc. When numerical range is described in this article, unless otherwise stated, the scope is intended to include its end value and all integers and fractions within the scope. In the present application specification and claims, range limitation can be combined and / or interchanged, if these ranges are not otherwise stated, include all sub-ranges contained therein.

[0032] The indefinite articles "a" and "an" before the elements or components of the present invention have no limitation on the quantity requirements (i.e. the number of occurrences) of the elements or components. Therefore, "a" or "an" should be interpreted as including one or at least one, and the elements or components in the singular form also include the plural form, unless the quantity obviously refers to the singular form only.

[0033] The "one embodiment" or "embodiment" of the present invention refers to a specific feature, structure or characteristic that can be included in at least one implementation of the present invention. The "in one embodiment" that appears in different places in this specification does not refer to the same embodiment, nor is it a separate or selective embodiment that is mutually exclusive with other embodiments.

[0034] The endpoints and any values ​​of the ranges disclosed in the invention are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in this article.

[0035] Example 1

[0036] The preparation method of the high-efficiency degradable low-density magnesium-based alloy of this embodiment is carried out according to the following steps:

[0037] (1) Weighing materials: weigh pure Mg, pure Li, Mg-30% Gd master alloy and Mg-30% Ni master alloy according to the composition and content of Li: 8wt%, Gd: 4wt%, Ni: 1.5wt%, and the balance Mg;

[0038] (2) Melting: The above raw materials are placed in a crucible, and the vacuum induction melting furnace is filled with pure Ar gas for protection. Then, the raw materials in the crucible are heated from room temperature to 200°C and kept at this temperature for 5 min, then heated to 450°C and kept at this temperature for 5 min, and finally heated to 720°C and kept at this temperature for 5 min to obtain a molten alloy;

[0039] (3) Casting: Pour the above alloy liquid into an iron mold to obtain an alloy ingot.

[0040] Example 2

[0041] The preparation method of the high-efficiency degradable low-density magnesium-based alloy of this embodiment is carried out according to the following steps:

[0042] (1) Weighing materials: weigh pure Mg, pure Li, Mg-30% Gd master alloy and Mg-30% Ni master alloy according to the composition and content of Li: 8wt%, Gd: 4wt%, Ni: 1wt%, and the balance Mg;

[0043] (2) Melting: The above raw materials are placed in a crucible, and a vacuum induction melting furnace is filled with pure Ar gas for protection. The raw materials in the crucible are then heated from room temperature to 200°C and kept at this temperature for 5 min, then continued to be heated to 450°C and kept at this temperature for 5 min, and finally heated to 720°C and kept at this temperature for 5 min to obtain a molten alloy;

[0044] (3) Casting: Pour the above alloy liquid into an iron mold to obtain an alloy ingot.

[0045] Example 3

[0046] The preparation method of the high-efficiency degradable low-density magnesium-based alloy of this embodiment is carried out according to the following steps:

[0047] (1) Weighing materials: weigh pure Mg, pure Li, Mg-30% Gd master alloy and Mg-30% Ni master alloy according to the composition and content of Li: 8wt%, Gd: 4wt%, Ni: 0.5wt%, and the balance Mg;

[0048] (2) Melting: The above raw materials are placed in a crucible, and a vacuum induction melting furnace is filled with pure Ar gas for protection. The raw materials in the crucible are then heated from room temperature to 200°C and kept at this temperature for 5 min, then continued to be heated to 450°C and kept at this temperature for 5 min, and finally heated to 720°C and kept at this temperature for 5 min to obtain a molten alloy;

[0049] (3) Casting: Pour the above alloy liquid into an iron mold to obtain an alloy ingot.

[0050] Comparative Example:

[0051] The preparation method of the magnesium-based alloy of this comparative example is carried out according to the following steps:

[0052] (1) Weighing materials: weigh pure Mg, pure Li and Mg-30%Gd master alloy according to the composition and content of Li: 8wt%, Gd: 4wt%, and the balance Mg;

[0053] (2) Melting: The above raw materials are placed in a crucible, and a vacuum induction melting furnace is filled with pure Ar gas for protection. Then, the raw materials in the crucible are heated from room temperature to 200° C. and kept at this temperature for 5 min, then heated to 450° C. and kept at this temperature for 5 min, and finally heated to 720° C. and kept at this temperature for 5 min to obtain a molten alloy;

[0054] (3) Casting: Pour the above alloy liquid into an iron mold to obtain an alloy ingot.

[0055] The magnesium-based alloys obtained in Examples 1-3 and Comparative Example 1 were machined into fracturing balls, and the following performance tests were performed. The results are as follows:

[0056] Figure 1 The optical microscopic images of the magnesium-based alloy fracturing balls obtained in Examples 1-3 and Comparative Example 1 are shown in FIG. Figure 1 It can be seen that a two-phase Mg-Li alloy is formed, α-Mg mostly appears at the grain boundary and partly appears inside the crystal, and LPSO appears in α-Mg. LPSO is strip-shaped, and the black dots are Gd-rich phases.

[0057] Figure 2 The XRD diffraction patterns of the magnesium-based alloy fracturing balls obtained in Examples 1-3 and Comparative Example 1 are shown in FIG. Figure 2 It can be seen that the alloy is a two-phase Mg-Li alloy, and LPSO, GdNi3 and GdMg3 appear after adding Ni.

[0058] Figure 3 The compressive stress-strain curves of the magnesium-based alloy fracturing balls obtained in Examples 1-3 and Comparative Example 1 at 25°C are shown in Table 1. Figure 3 It can be seen that compared with comparative example 1, the mechanical properties and plastic toughness are improved to a certain extent.

[0059] Figure 4 is the weight loss rate of the magnesium-based alloy fracturing ball obtained in Examples 1-3 and Comparative Example 1 in a 3% KCl solution at 25°C, from Figure 4 It can be seen that the weight loss rate is significantly faster than that of the material in Comparative Example 1.

[0060] Figure 5 The hydrogen evolution volume and hydrogen evolution rate of the magnesium-based alloy fracturing balls obtained in Examples 1-3 and Comparative Example 1 in a 3% KCl solution at 25°C over time are shown in Table 1. Figure 5 It can be seen that compared with the material in Comparative Example 1, the hydrogen evolution volume is higher and the hydrogen evolution rate is faster.

[0061] The above are only preferred specific embodiments of the present invention, which are all different implementations based on the overall concept of the present invention, and the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A method for efficiently degrading low-density magnesium-based alloys, characterized in that: Its composition by mass fraction is: Li: 5.7-10.3%, Gd: 2-6%, Ni: 0.5-1.5%, and the balance is Mg.

2. The magnesium-based alloy according to claim 1, characterized in that The composition by mass fraction is: Li: 8%, Gd: 4%, Ni: 1.5%, and the balance is Mg.

3. The method for preparing a highly degradable low-density magnesium-based alloy according to claim 1 or 2, characterized in that: Follow these steps: Pure Mg, pure Li, Mg-Gd alloy and Mg-Ni alloy are used as raw materials, which are melted in a vacuum induction melting furnace and then cast into shape.

4. The method according to claim 3, characterized in that: Mg-Gd alloy is Mg-30%Gd, and Mg-Ni alloy is Mg-30%Ni.

5. The method according to claim 3, characterized in that: Pure Ar was used as protective gas during the smelting process.

6. The method according to claim 3, characterized in that Melting process: heat from room temperature to 150-200℃ and keep warm for 5 minutes, then continue to heat to 400-450℃ and keep warm for 5 minutes, and finally heat to 720℃ and keep warm.

7. Use of the highly degradable low-density magnesium-based alloy according to claim 1 or 2 in the preparation of fracturing balls.

8. A method for preparing a fracturing ball, characterized in that: The high-efficiency degradable low-density magnesium-based alloy according to claim 1 or 2 is made into a fracturing ball by mechanical processing.

9. The fracturing ball prepared by the method according to claim 8, characterized in that: Its compressive strength is 100-150MPa.

10. The fracturing ball according to claim 9, characterized in that: The dissolution rate in 3% KCl aqueous solution at 25°C is 0.155-0.36 mg / cm 2 ·min, hydrogen evolution rate is 0.16-0.37mL / cm 2 ·min.